STUDIES ON CREOSOTE AS A WOOD PRESERVATIVE FOR MARINE STRUCTURES PART I INCORPORATION OF ARSENIC IN CREOSTE AT VARIOUS TEMPERATURE - NAIR, N UNNIKRISHNAN; PILLAI, A.G GOPALAKRISHNA; BALASUBRAMANYAN, R (Fishery Technology, 2025)
A detailed study of the fortification of normal creosote and low temperature creosote with As 2 0 3 at 40°C, 50°C, 60°C, 70°C, 80°C & 90°C was can-ied out. When compared to normal creosote, low temperature creosote has been found to combine more easily with As2 0 3 when temperature was . raised from 40 to 90°C. The incorporated arsenic values obtained shows that low temperature creosote with high phenolic content, retains considerably more As 2 0 3 and a maximum of 0.2180% wjw can be incorporated in low temperature creosote at 90°C.